TECHNOCULTURAL INNOVATION IN WOMEN’S ENTREPRENEURSHIP: TRANSFORMING 3D KARAWO EMBROIDERY DIGITALLY - Yulinda L. Ismail; Haris Danial; Indhitya R. Padiku; Riansyah Mahmud (Community Development Journal : Jurnal Pengabdian Masyarakat, 2025)
Karawo embroidery represents an emblematic cultural heritage of Gorontalo Province, celebrated for its distinctive aesthetic qualities, intricate craftsmanship, and profound philosophical values. Nevertheless, despite supportive regulations, such as Gorontalo Provincial Regulation No. 4 of 2017 and the formal designation of Karawo Day, artisans continue to face persistent challenges related to generational continuity, branding, and the integration of modern technology. These issues are evident among the women’s Karawo artisan group in Bongohulawa Village, Bongomeme District, which holds considerable potential but remains underdeveloped due to constraints in design innovation, business management, legal status, and digital marketing capacity. To respond to these challenges, a structured program was implemented to foster women-led micro, small, and medium-sized enterprises (MSMEs) producing custom 3D Karawo through entrepreneurship and digitalization. The program encompassed socialization activities, intensive training in both manual and digital motif design using the Crosti application with 3D innovations, MSME management, 3D Karawo production, and business legalization. It also incorporated technology adoption in production and digital marketing through social media, online marketplaces, and Google Sites-based branding platforms, followed by mentoring, evaluation, and sustainability planning focused on network building and long-term marketing strategies. The results are substantial: ten new patterns emerged, 80 percent of participants mastered Crosti digitalization, business registrations and partnerships were secured, branded prototypes were produced, e-commerce accounts and online catalogs were launched, and an interactive digital platform was developed.